Sistem Penyiram Tanaman Otomatis Menggunakan RTC Dan Sensor Hujan - Haris Yuana; Zunita Wulansari; Mukh Taofik Chulkamdi (J-INTECH ( Journal of Information and Technology), 2023)
A plant is a plant that is maintained or maintained in a medium to benefit or be harvested at any given time. The growth process requires regular watering so that plants can grow and bear good fruit. The automatic crop watering system is a study aimed at increasing the efficiency of irrigation management in agriculture automatically so that it can assist farmers in Indonesia. Where farmers are currently experiencing problems in the watering problem, there is a delay in watering the crops. This study integrated Real-Time Clock (RTC) and rain sensors as major elements in plant watering automation systems. RTC is used to set the watering schedule based on a predetermined time, while the rain sensor serves as an automatic controller to stop watering when rain is detected. The system development method involves designing well-integrated hardware and software. LCD display screens are also used in systems to provide additional information to optimize the amount of water required by plants. NodeMcu is used as a system controller so that no errors occur in scheduling plant watering. Research methods using RnD (Research and Development). The implementation of an automated crop watering system is expected to contribute to the management of water resources and energy, improve agricultural efficiency, and provide environmentally friendly and petrifying solutions for farmers across Indonesia to produce crops. Test results show that this system is capable of optimizing plant watering based on environmental conditions, thus reducing water waste and increasing plant productivity on a sustainable basis.